2018
DOI: 10.1038/s41467-018-05102-x
|View full text |Cite
|
Sign up to set email alerts
|

Creating two self-assembly micro-environments to achieve supercrystals with dual structures using polyhedral nanoparticles

Abstract: Organizing nanoparticles into supercrystals comprising multiple structures remains challenging. Here, we achieve one assembly with dual structures for Ag polyhedral building blocks, comprising truncated cubes, cuboctahedra, truncated octahedra, and octahedra. We create two micro-environments in a solvent evaporation-driven assembly system: one at the drying front and one at the air/water interface. Dynamic solvent flow concentrates the polyhedra at the drying front, generating hard particle behaviors and leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…The asymmetric peak of CuO NPs was confirmed by the presence of a peak at 590 cm –1 [58]. The high packing efficiency of self-assembled nanocubes was supported in earlier studies [59]. Nanocubes with high packing density are preferable for drug delivery and interaction with cells and biomolecules [60].…”
Section: Discussionmentioning
confidence: 76%
“…The asymmetric peak of CuO NPs was confirmed by the presence of a peak at 590 cm –1 [58]. The high packing efficiency of self-assembled nanocubes was supported in earlier studies [59]. Nanocubes with high packing density are preferable for drug delivery and interaction with cells and biomolecules [60].…”
Section: Discussionmentioning
confidence: 76%
“…Consequently, although core nanoparticles still matter, "patchiness" can completely alter the interaction dynamics and govern the final superlattice structures. The decades of extensive studies on conventional nanoparticles without patches have revealed the factors determining interaction between nanoparticles and their packing behavior, including shape anisotropy [23,24], crystal facets [25], and entropy of the system [26,27]. In recent years, both in experiment and theory, researchers have been trying to identify the design parameters for the patches to direct assembly behaviors of patchy nanoparticles.…”
Section: Preparation Of Patchy Nanoparticles 21 Design Rules Of Corementioning
confidence: 99%
“…Their importance lies in the fact that artificially designed architectures with the desired morphologies and sizes may provide a variety of unexpected electronic, optical, sensing, and catalytic functions that differ from those of their small building blocks [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. To produce inorganic NP-based nano- and microstructures with desired dimensions [ 18 , 19 , 20 , 21 , 22 ], top-down and bottom-up strategies have been widely developed, for example, lithographic and patterning techniques [ 23 , 24 , 25 , 26 ], electrospinning [ 27 , 28 ], the Langmuir–Blodgett technique [ 29 , 30 ], solvent evaporation-driven self-assembly [ 31 , 32 , 33 ], and the polymer-mediated self-assembly of NP building blocks [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Most of the bottom-up polymer-mediated NP assembly strategies require the laborious introduction of specific functional groups on NP surfaces, the addition of certain salts, pH adjustment, etc.…”
Section: Introductionmentioning
confidence: 99%